Preparation and Pb(II) Adsorption Properties of Crosslinked Pectin-Carboxymethyl Chitosan Film - Budi Hastuti; Mudasir Mudasir; Dwi Siswanta; Triyono Triyono (Indonesian Journal of Chemistry, 2015)
A modified pectin has been synthesized by reacting/combining -OH group among pectin and chitosan with BADGE (Bisphenol A diglycidyl ether) crosslinker agent. The structure and morphology of the new material were characterized by Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM) and X-ray Diffraction (XRD) analysis. Thermogravimetric studies showed an improvement in thermal characteristic. Adsorption experiments were performed in batch processes; sorption isotherms and kinetics were also studied. The Langmuir and Freundlich adsorption isotherm models were applied to describe the isotherms and isotherm constants for the adsorption of Pb(II) ion onto adsorbent pectin-carboxymethyl chitosan-BADGE (pec-CMC-BADGE). The dynamic study showed that the sorption process followed the second-order kinetic equation. Result indicated also that Pb(II) ion uptake could be well described by the Langmuir and Freundlich adsorption model of pec-CMC-BADGE and CMC with DG° of 25.3 and 23.1 kJ mol-1,respectively, while that of pectin followed Freundlich isotherm with DG° of 16.6 kJ mol-1.